2019
DOI: 10.21037/atm.2019.11.105
|View full text |Cite|
|
Sign up to set email alerts
|

CDK14 involvement in proliferation migration and invasion of esophageal cancer

Abstract: Background: CDK14 has significant involvement in tumorigenesis of cancers including hepatocellular carcinoma, gastric carcinoma and breast cancer. In esophageal cancer, CDK14 is useful as a prognostic marker and as a predictor of response to chemotherapy. However, the exact mechanism of CDK14 n chemotherapy for esophageal squamous cell carcinoma (ESCC) has not been explored. Methods: Western blots and immunohistochemistry (IHC) analysis were performed to analyse the expression of CDK14 in ESCC. Co-immunoprecip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…As the host gene of circCDK14, CDK14 acts as a cyclin-dependent kinase that regulates cell cycle progression and cell proliferation. CDK14 involves in tumorigenesis of various cancers including glioma [30,32,33]. Studies shows that the interaction between CDK14 and cyclin Y can promote noncanonical Wnt signaling in human hepatocellular carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…As the host gene of circCDK14, CDK14 acts as a cyclin-dependent kinase that regulates cell cycle progression and cell proliferation. CDK14 involves in tumorigenesis of various cancers including glioma [30,32,33]. Studies shows that the interaction between CDK14 and cyclin Y can promote noncanonical Wnt signaling in human hepatocellular carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our transcriptional analysis suggests some potential mechanisms. Examples include transcripts of genes that promote growth and invasiveness in ESCC cells, such as Nrp2, Cdk14 and Sox9 which are more highly expressed in Notch1 wild type than null esophageal cells [35][36][37] . Conversely, transcription of Cldn7 which represses ESCC invasiveness is upregulated in Notch1 -/cells 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that CDK14 is the main regulator of cyclin-Y-dependent Wnt signaling [ 11 , 34 ], and we observed exceedingly low levels of CDK14 specifically in the intestinal epithelium [ 22 , 23 ]. CDK14 has been shown to interact with other cyclins as well, such as cyclin B to activate the Wnt pathway in breast cancer [ 35 ], cyclin D3 to regulate cell cycle progression and proliferation in mammalian cells [ 36 ], and the CDK7/cyclin H complex to regulate proliferation and migration in esophageal cancer [ 37 ]. It should be noted that previous studies suggested functional redundancy among the human PFTAIRE/PCTAIRE family kinases (CDK 14–18) [ 11 , 38 ].…”
Section: Discussionmentioning
confidence: 99%